A Monte Carlo simulation model of supply chain risk due to natural disasters. (4th September 2008) - Miller, Holmes E.; Engemann, Kurt J.
In this paper we present a model that simulates the effects of natural disaster risks for a hypothetical three tier supply chain. Drawing on concepts from reliability theory and capacity analysis, the model is structured such that diminutions of service capacity at nodes lower in the supply chain can affect higher tier nodes. The model is used to examine various scenarios, including examining correlation among node locations; the effectiveness of disaster recovery plans; and dual sourcing. In addition, the size of the lower tier of the supply chain is expanded and the ensuing results are compared to those for leaner supply chains.